Service Quality and Healthcare Costs as Predictors of Patient Satisfaction in Indonesia’s National Health Insurance - Hana Dwi Jayanti; Gede Sri Darma (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to investigate and analyze the influence of administrative services, medical services, and costs on the loyalty of JKN participants, with satisfaction acting as a mediating variable. A quantitative research design was employed to examine these relationships. The empirical findings reveal that satisfaction exerts a significant positive effect on loyalty. Moreover, medical service quality and cost perception demonstrate a significant impact on satisfaction, highlighting their critical role in enhancing customer experience. However, the direct effects of medical services and costs on loyalty were found to be statistically insignificant, suggesting that loyalty is predominantly mediated through satisfaction. In contrast, administrative services exhibited no significant influence on either satisfaction or loyalty, indicating their limited contribution to fostering long-term customer relationships. Overall, these results underscore the strategic importance of improving medical service quality and ensuring a transparent cost structure to enhance satisfaction, which ultimately strengthens participant loyalty within the JKN program.